Popular Food Colors for Sustainable Corrosion Inhibition of Mild Steel in 0.5 M H2SO4: Electrochemical and Surface Morphological Investigation - Tiwari P.; Pal S.; Ji G.; Prakash R. (My University, 2025)
One of the applications of azo compounds is as food colors in various countries. The azo dyes have interesting chemical structures and hence attract attention to test them for corrosion prevention applications. Three azo dyes namely Amarnyth (AH), Allura red (AD) and Sunset Yellow (SW) are tested for inhibition of mild steel (MS) corrosion in 0.5 M H2SO4. The techniques used for the examination are Fourier Transform Infrared spectroscopy (IRS), UV–Visible spectroscopy (UV–Vis), electrochemical impedance spectroscopy (EIS), linear polarization resistance (Rl), Tafel polarization curves (TC), scanning electron microscopy (SEM) and atomic force microscopy (AFM). The AH provides inhibition of 90%, whereas SW and AD offer inhibition of 80% and 78% respectively. The inhibition was realized because of MS coverage via adsorption of azo dyes of in sulfuric acid solutions, which is evidently visible in SEM and AFM images. The azo dyes adsorb on MS as per Langmuir isotherm. A schematic illustration is also provided based on the findings of this work. Graphical abstract: [Figure not available: see fulltext.]. © 2022, The Tunisian Chemical Society and Springer Nature Switzerland AG.